The use of the Körperkoordinationstest für Kinder in the talent pathway in youth athletes: A systematic review. Issue 9 (September 2019) - O'Brien-Smith, J.; Tribolet, R.; Smith, M.R.; Bennett, K.J.M.; Fransen, J.; Pion, J.; Lenoir, M.
Abstract: Objectives: Identifying talented athletes from an early age to accelerate their development requires the investment of substantial resources. Due to the need for multifactorial approaches to talent identification, motor competence assessments are increasingly prevalent in contemporary testing batteries. Therefore, the aim of this review was to evaluate the literature on the use of a product-oriented motor competence assessment tool, the Körperkoordinationstest für Kinder (KTK) in the talent pathway and determine whether it is warranted in such programs. Methods: Three electronic databases (i.e. PubMed, SPORTDiscus and Web of Science) were searched for studies that used at least one component of the KTK to assess motor competence for talent detection, identification, development and selection in athletic populations. A total of 21 articles were included in the review, of which seven used the full version of the KTK and 14 used modified versions or individual components of the battery. The quality of included studies was assessed using a modified version of the Joanna Brigg's Institute Critical Appraisal Checklist. Results: The analysed literature suggests that the KTK can successfully distinguish between athletes of different competition levels and across different sporting domains, however, findings should be interpreted with caution due to the cross-sectional nature of the studies. Furthermore, the moving sideways subtest displayed the greatest discriminative power for athletes of different competition levels. Motor competence was not affected by maturation and did not differ between genders or playing positions. Conclusions: Collectively, these findings suggest that the KTK is a useful motor competence assessment in the talent pathway.